2014
DOI: 10.1186/s12977-014-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of genomic RNA (gRNA) dimerization and packaging determinants of mouse mammary tumor virus (MMTV)

Abstract: BackgroundOne of the hallmarks of retroviral life cycle is the efficient and specific packaging of two copies of retroviral gRNA in the form of a non-covalent RNA dimer by the assembling virions. It is becoming increasingly clear that the process of dimerization is closely linked with gRNA packaging, and in some retroviruses, the latter depends on the former. Earlier mutational analysis of the 5’ end of the MMTV genome indicated that MMTV gRNA packaging determinants comprise sequences both within the 5’ untran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(92 citation statements)
references
References 85 publications
(130 reference statements)
5
87
0
Order By: Relevance
“…We have recently shown that the entire 5ʹ UTR and the first 120 nt of gag are required for efficient MMTV gRNA packaging and propagation [23,24]. Furthermore, these sequences were predicted to fold into higher order structures comprising of several structural motifs, which were validated by SHAPE (selective 2ʹ-hydroxyl acylation analyzed by primer extension [25]. …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that the entire 5ʹ UTR and the first 120 nt of gag are required for efficient MMTV gRNA packaging and propagation [23,24]. Furthermore, these sequences were predicted to fold into higher order structures comprising of several structural motifs, which were validated by SHAPE (selective 2ʹ-hydroxyl acylation analyzed by primer extension [25]. …”
Section: Introductionmentioning
confidence: 99%
“…A distinguishing feature of the SHAPE-validated structure of the MMTV packaging signal RNA is the presence of a bifurcated stem loop 4 (SL4) containing a palindromic sequence (pal II; 5ʹ CUGCAG 3ʹ) and a 9 nt stretch (5ʹGGAGAAGAG 3ʹ) of single-stranded purines (ssPurines) in adjacent apical loops [25]. Both pal II and ssPurines are phylogenetically conserved in eight different strains of MMTV at the sequence as well as the secondary structural levels [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations